Levantamiento del secreto de las comunicaciones a agraviados y testigos y el debido proceso en Trujillo durante 2017 - Toledo Torres, Emilio David Ricardo (2019)
This thesis aims to determine how the rights-restrictive measure of lifting of the right to secrecy in communications against victims and witnesses supposes a violation of the principle of due process. To that end, dogmatic, jurisprudential and normative backgrounds have been checked and a balancing of rights between the two variables has been made in order to come up with a legislative initiative to solve the aforementioned problem. The information available in the subject is limited, especially in national search, hence the investigation falling in the exploratory category. This research work is divided in five parts. The first one approaches the formal aspects of motivation, background, justification, problem and hypothesis, objectives, as well as the used materials and methods. The second part develops the theoretical framework in five chapters that include the new criminal process model and the due process, the subjects of the criminal process plus the witness, the rights-restrictive measures and the LSC, the crime of extortion and, finally, the problematic confrontation between the LSC applied to victims and witnesses and the due process. The third part is an additional chapter that includes a real-world case that serves to illustrate the points explained throughout the thesis. Part four aims to gather and list the conclusions that are product of the investigation. Lastly, the recommendations are treated in part five, where attention is drawn to the proposed modification of the Criminal Procedure Law for the inclusion of the LSC measure.